Bukti Empiris Praktik Perpajakan Dan Pembukuan Atas Transaksi Kartu Kredit Pemerintah Di Indonesia - Joko Sumantri (Politeknik Keuangan Negara STAN, 2022)
This paper examines the practice applied in the payment of Indonesian government spending using KKP (Government Credit Card-Kartu Kredit Pemerintah) which is associated with fulfilling the obligations of the expenditure treasurer. In the discussion, the research tries to understand how the practices that occur and should be in withholding taxes, writing receipts and completeness of proof of payment, and the bookkeeping mechanism carried out by the treasurer of expenditures for payments using KKP. Using qualitative methods, we found that there were several scenarios of tax deductions, regulations that set different time limits for tax withholding and deposit, and modified bookkeeping of expenditure treasurer transactions for practical purposes in SAKTI (Sistem Aplikasi Keuangan Tingkat Instansi).